2009
DOI: 10.1128/iai.01207-08
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Mechanisms Contribute to the Robust Rapid Gamma Interferon Response by CD8+T Cells duringListeria monocytogenesInfection

Abstract: A subset of CD8؉ T cells can rapidly secrete gamma interferon (IFN-␥) in an antigen-independent and interleukin-12 (IL-12)-and IL-18-dependent manner within 16 h of infection with the intracellular bacterial pathogen Listeria monocytogenes. This rapid IFN-␥ response is robust enough to be detected directly ex vivo and is not observed following infection with intracellular bacterial pathogens that remain sequestered within host cell vacuoles. We demonstrate here that three distinct pathways can lead to rapid se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…Whether this "more direct NLRP3 activation" depends on a direct interaction of LLO and NLRP3, or more likely on still unidentified cytosolic mediator molecules upstream of NLRP3, is unknown. The hypothesis that LLO activates host cell responses through different pathways is supported by recently published results suggesting multiple mechanisms of LLO-stimulated, IL-18-dependent IFN-g production (56).…”
Section: Discussionsupporting
confidence: 55%
“…Whether this "more direct NLRP3 activation" depends on a direct interaction of LLO and NLRP3, or more likely on still unidentified cytosolic mediator molecules upstream of NLRP3, is unknown. The hypothesis that LLO activates host cell responses through different pathways is supported by recently published results suggesting multiple mechanisms of LLO-stimulated, IL-18-dependent IFN-g production (56).…”
Section: Discussionsupporting
confidence: 55%
“…DC derived from murine bone marrow with GM-CSF are known to be phenotypically heterogeneous (23) and most closely related functionally to inflammatory, monocyte-derived DC (48) Although our data implicate defective LLO function in DC phagosomes, they must be considered in light of the fact that the precise mechanism by which LLO forms pores in phagosomal membranes is not clear and is known to be influenced by multiple bacterial and host-derived factors (37). Further, LLO has the ability to transiently delay phagosome/lysosome fusion in macrophages (39), as well as to transmit signals to the host cell (7,29). Therefore, the factors that influence LLO activity in DC are likely to be complex and will require further study.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Previous studies conducted on the burn P aeruginosa model revealed the existence of myelosuppression in addition to neutrophil consumption and apoptosis during sepsis. 13,29 Interestingly, a recent study from Zhu et al showed that Listeria monocytogences, a Gram-positive bacteria with a TLR4 agonist component, 30,31 can induce myelosuppression and neutropenia correlating with lethality. 32 Although these studies clearly indicated the presence of a myelosuppressive activity during lethal sepsis, they were limited to the analysis of progenitor colonies and terminal differentiation of BM myeloid cells, 33,34 and the mechanisms mediating this process were not elucidated.…”
Section: Discussionmentioning
confidence: 99%